(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Using Maruti Suzuki cars as an example, this study delves into the complex web of relationships between price sensitivity, advertising effectiveness, and customer behaviour in the Nagpur car market. Maintaining sales growth and a competitive advantage is a problem for Maruti Suzuki, a prominent participant in the Indian automobile industry, as it must navigate customer preferences and market dynamics. Using a combination of survey data, interview transcripts, and statistical analysis, this research seeks to answer this question by illuminating the factors that influence car buyers’ actions in Nagpur. The first part of the study looks at how advertising makes people feel and think about Maruti Suzuki cars. The effectiveness of advertisements, the desire to buy, and the ability to remember brands are all measured by means of interviews and surveys administered to the general public. The research also looks at how price sensitive customers are by examining how they react to Maruti Suzuki’s pricing tactics, sales, and incentives. Insights gained from this study will help industry players like Maruti Suzuki improve their marketing tactics and boost sales in the Nagpur car market. Automakers may improve their marketing strategies to reach their target customers more effectively by learning how price sensitivity, advertising effectiveness, and consumer behaviour interact with each other. This knowledge will help them build stronger brand loyalty and engagement. In the end, this study adds to what is already known about automobile marketing by demonstrating, via data, what variables impact customer behaviour in the automotive industry in Nagpur. The study’s findings may help car companies like Maruti Suzuki and others make better strategic decisions, such how to improve their marketing tactics to boost sales and compete better in Nagpur and beyond.